The Degree of Using Educational Play by Arabic Teachers in Al-Ras Governorate - Al-Tarisi, Hasah Jihaz Zaban; Al-Tamimi, Ghada Nasser (Journal of Educational and Psychological Sciences, 2021)
This study aims to uncover the extent of usage of educational play skills by Arabic language instructors of Al-Ras educational governorate. The sample of the study consisted of 172 Arabic female teachers who were selected purposively. To this end, the researcher has constructed a questionnaire that entailed educational play skills. The questionnaire has been validated and ensured for reliability and validity. The study findings revealed that Arabic instructors in Al-Ras governorate are using evaluation, action, and planning skills of play in a high degree. In light of these findings, the researcher provides many recommendations, and the major one is the need to enhance utilizing educational play skills by Arabic teachers in their instruction.